Sinterização diferencial e auto-tensionamento: efeitos na condutividade elétrica da Zircônia estabilizada com Ítria - Goulart, Celso Antonio (2019)
Recent researches indicate the possibility of increasing Yttria Stabilized Zirconia (YSZ) electrical conductivity by generating stress states in the material, by applying external loads or by its insertion in multilayer systems. On the other hand, in the past decades, several papers have shown that the formation of defects and the incomplete densification in ceramic composites containing rigid inclusions are related to the emergence of stresses in the matrix due to the phenomena of restricted and differential sintering. In this work, these phenomena were induced in 8 mol% Yttria Stabilized Zirconia (8YSZ) matrices by means of controlled addition of different contents of rigid inclusions of sintered ceramic particles with different shapes (spherical and jagged), sizes (60-200 µm) and compositions (8YSZ, 3YSZ and alumina). The effects of residual stresses after sintering on the electrical conductivity of 8YSZ were evaluated and, under specific conditions, the addition of 1 vol% of YSZ irregular rigid inclusions led to an increase of 36% in total electrical conductivity compared to samples without inclusions. Computer simulations provided additional information on the development and evolution of stresses during sintering.